T2-Weighted Image-Based Radiomics Signature for Discriminating Between Seminomas and Nonseminoma - Zhang, Peipei; Feng, Zhaoyan; Cai, Wei; You, Huijuan; Fan, Chanyuan; Lv, Wenzhi; Min, Xiangde; Wang, Liang (Frontiers in Oncology, 2019)
Objective: To evaluate the performance of a T2-weighted image (T2WI)-based radiomics signature for differentiating between seminomas and nonseminomas. Materials and Methods: Thirty-nine patients with testicular germ-cell tumors (TGCTs) confirmed by radical orchiectomy were enrolled, including 19 cases of seminomas and 20 cases of nonseminomas. All patients underwent 3T magnetic resonance (MR) imaging before radical orchiectomy. Eight hundred fifty-one radiomics features were extracted from the T2WI of each patient. The intra- and interclass correlation coefficient was used to select features with excellent stability and repeatability. Then, we used the minimum-redundancy maximum-relevance (mRMR) and the least absolute shrinkage and selection operator (LASSO) algorithms for feature selection and radiomics signature development. Receiver operating characteristic curve analysis was used to evaluate the diagnostic performance of the radiomics signature. Results: Five features were selected to build the radiomics signature. The radiomics signatures were significantly different between the seminomas and nonseminomas (p<0.01). The area under the curve (AUC), sensitivity, and specificity of the radiomics signature for discriminating between seminomas and nonseminomas were 0.979 (95% CI: 0.873 - 1.000), 90.00 (95% CI: 68.3 - 98.8), and 100.00 (95% CI: 82.4 - 100.0), respectively. Conclusion: T2WI-based radiomics features have the potential to noninvasively discriminate between seminomas and nonseminomas.